Complex karyotype and translocation t(4;14) define patients with high-risk newly diagnosed multiple myeloma: results of CMG2002 trial - Nemec, Pavel; Zemanova, Zuzana; Kuglik, Petr; Michalova, Kyra; Tajtlova, Jana; Kaisarova, Petra; Oltova, Alexandra; Filkova, Hana; Holzerova, Milena; Balcarkova, Jana; Jarosova, Marie; Rabasova, Jana; et al. (Leukemia & lymphoma, 2012)
The prognostic impact of chromosomal abnormalities was evaluated by fluorescence in situ hybridization with cytoplasmic immunoglobulin light chain staining (cIg-FISH) and by classical metaphase cytogenetics in a cohort of 207 patients with newly diagnosed multiple myeloma who were treated with high-dose therapy followed by autologous stem cell transplantation in the CMG2002 clinical trial. The incidence of chromosomal abnormalities detected by FISH was as follows: 52.7% for del(13)(q14), 6.5% for del(17)(p13), 18.6% for t(11;14)(q13;q32), 22.8% for t(4;14)(p16;q32) and 45.7% for gain(1)(q21). Metaphase cytogenetic analysis revealed a complex karyotype in 19.1% and hyperdiploidy in 21.7% of patients. The overall response rate was not influenced by the presence of any studied chromosomal abnormality. Patients with a complex karyotype, those with translocation t(4;14) and those with gain of the 1q21 locus had a shorter time to progression (TTP) and overall survival (OS). Other genomic changes such as translocation t(11;14) and del(13q) had less impact on TTP and OS. In multivariate analysis, complex karyotype, translocation t(4;14) and β(2)-microglobulin level > 2.5 mg/L were independent prognostic factors associated with poor overall survival. Their unfavorable prognostic impact was even more pronounced if they were present in combination. Patients with t(4;14) present together with a complex karyotype had the worst prognosis, with a median OS of only 13.2 months, whereas patients with a normal karyotype or karyotype with ≤ 2 chromosomal changes had the best outcome, with 3-year OS of 85.9%. In conclusion, complex karyotype, gain of 1q21 region and translocation t(4;14) are major prognostic factors associated with reduced survival of patients with newly diagnosed multiple myeloma treated with autologous stem cell transplantation.
Keywords: transplantace hematopoetických kmenových buněk; Chromosomes, Human, Pair 14; Humans; Transplantation, Autologous; translokace genetická; lidé středního věku; lidské chromozomy, pár 4; cytogenetické vyšetření; Hematopoietic Stem Cell Transplantation; Multiple Myeloma; Female; Aged; dospělí; autologní transplantace; Translocation, Genetic; senioři; lidé; lidské chromozomy, pár 14; mnohočetný myelom; Adult; chromozomální aberace; ženské pohlaví; Chromosome Aberrations; Male; Middle Aged; prognóza; incidence; Incidence; karyotypizace; Chromosomes, Human, Pair 4; míra přežití; Cytogenetic Analysis; mužské pohlaví; Karyotyping; Prognosis; Survival Rate